Anatomia, 1838 (Hawaiian text with English translation) - Judd, Gerrit P. (University of Hawaii Press, 2003)
Anatomia is the only medical textbook written in the Hawaiian language. Gerrit P. Judd, for a time the only medical missionary in the Islands, wrote the text in 1838 to teach basic anatomy to Hawaiians enrolled at the Mission Seminary (Lahainaluna School). Working from a standard elementary textbook of the time, Judd provided his students with more than a simple, straight translation. Rather than "Hawaiianize" Latin or English names and terms, he devised new vocabulary and explained medical functions and practices in words that would be readily understood by a Hawaiian. Judd's use of Hawaiian terms and descriptions gives us insights into native cultural and healing practices in the early decades of the nineteenth century. Anatomia is a valuable addition to the growing collection of translations on native health and will be greatly appreciated by linguists, historians, and students of Hawaiian language and culture.